Freud’s Psychoanalysis of the Three Different Components of the Human Mind through the Main Characters in Don’t Worry Darling Movie - Zahira, Arizky Raihannah; Parthama, I Gusti Ngurah; Mulyana, Novita (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This study entitled “Freud Psychoanalysis of the Three Different Components of the Human Mind through the Main Characters in Don’t Worry Darling Movie” aims at the main characters’ personality in the movie. The purpose of the research is to describe and to explain the two main characters’ personalities using the proposed theory by Sigmund Freud (1923). This study focuses on the two main characters, Alice Chambers and Jack Chambers. The theories that are used to support this study are the relation between literature and psychology in a human life. The second supporting theory is the theory of Sigmund Freud on psychoanalysis components (1923). The data of this research are taken from the conversations between characters and the scenes taken in the ‘Don’t Worry Darling’ Movie. The method used to collect the data is the documentation method as well as the use of the note-taking technique. The method of analyzing the data is the qualitative method. The technique used to describe the analyzed data is the descriptive technique. The results of this research are that each character has their own id, ego, and superego in their life throughout the movie. The main characters revealed the three components through their own actions and words, which from these three components, the researcher is able to describe the characters’ personality. It is concluded that Alice Chambers’ personality is a character full of curiosity. As for Jack Chambers’ personality is an ambitious person but he tends to act reckless. The researcher explains more regarding the collected potential data with important meaning in the conclusion. Keywords: Psychoanalysis components of Sigmund Freud, Don’t Worry Darling, Id, Ego, Superego